Studi Awal Pemodelan Perlakuan Virotherapy Yang Menggunakan Virus Campak Pada Tumor Paru-Paru Tikus - Kartono, Agus; Sunjono, Sunjono; Arif, Ardian (BERKALA FISIKA, 2010)
The interaction model dynamics between tumor and viruses based on the interaction phenomenon between the three populations, namely: population of uninfected tumor cells, tumor cell population infected with the virus and the virus population. This study aimed to see the interaction between non-infected tumor cells, tumor cells infected with viruses and viruses, so it can be modeled using virotherapy treatment of measles virus in mouse lung tumors. Model parameters obtained from experimental data. Numerical Solution of the models suggest that the dose of the virus play an important role in determining the outcome of tumor therapy. Tumor growth can be slowed by using this virotherapy, but the tumor can not be killed as a whole. Keywords: model dynamics, virotherapy, measles virus, mouse lung tumors